Systematic Literature Review: Penyalahgunaan Narkoba di Kalangan Remaja dalam Perspektif Psikologi dan Islam - Purbanto, Hardy; Hidayat, Bahril (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2023)
Drug is a complex problem in Indonesia, marked by the increase of drug addict number and number of revealed cases. This badly impacts the community and country life in the future. One of factors which cause the increase of drug consumption in teenager is their attitude which ignores the values, norms, and applicable law. From Islamic point of view, drug abuse is included into ijtihad because it is not mentioned in Al-Qur’an and Hadits directly, but it is known as khamr. The purpose of this research was to identify the cause of drug abuse in teenagers and drug abuse in the perspective of Islam. The method employed was systematic literature review based on the articles published at Google Scholar and DOAJ in the last ten years (2012-2022) with keywords “drug abuse in teenagers” and “drug abuse in the perspective of Islam”. The results of this research showed that there were some factors which cause drug abuse in teenager such as internal factor and external factor. From Islamic point of view, drug (khamr) is haram and forbidden.